2017
DOI: 10.18182/tjf.306364
|View full text |Cite
|
Sign up to set email alerts
|

The importance of visitor characteristics and perceptions in the planning and effective management of protected areas: Kurşunlu Waterfall Natural Park example

Abstract: Korunan alanlar günümüzde çeşitli amaçlarla korunan ve kullanılan alanlardır. Bu alanların sürdürülebilir bir şekilde yönetilebilmesinde kilit faktörlerden birisi bu alanları kullanan ziyaretçileridir. Bu çalışmada ziyaretçi özellikleri ve algılarının korunan alanların planlanması ve etkin yönetimine etkileri araştırılmıştır. Çalışma alanı olarak Antalya İli sınırları içerisinde yer alan Kurşunlu Şelalesi Tabiat Parkı seçilmiştir. Çalışma kapsamında veri toplama yöntemleri olarak literatür tarama, anketmülakat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Their study showed that the ancient city of Assos is not famous yet, and its planner should consider visitor comments to prevent future problems regarding sustainable tourism. Akyol and Akbulut (2017), in their study on Kurs ¸unlu Nature Park, found that associating visitor characteristics and experience perceptions with the site's management would increase the effectiveness of managers in planning, using the site more efficiently and sustainably and making decisions.…”
Section: Jhti 74mentioning
confidence: 99%
See 1 more Smart Citation
“…Their study showed that the ancient city of Assos is not famous yet, and its planner should consider visitor comments to prevent future problems regarding sustainable tourism. Akyol and Akbulut (2017), in their study on Kurs ¸unlu Nature Park, found that associating visitor characteristics and experience perceptions with the site's management would increase the effectiveness of managers in planning, using the site more efficiently and sustainably and making decisions.…”
Section: Jhti 74mentioning
confidence: 99%
“…Visitor comments are also critical for sustainable museum management. The problems and suggestions stated by visitors enable managers to make healthier decisions regarding planning, using the area more efficiently and effectively and preventing potential issues regarding sustainable tourism (Bas ¸aran and Somuncu, 2021;Akyol and Akbulut, 2017). The proposed model offers a healthier perspective in evaluating visitor reviews and offering solutions.…”
Section: Practical Implicationsmentioning
confidence: 99%